2022
DOI: 10.3390/ijerph19095086
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attitudes and Satisfaction Concerning the COVID-19 Vaccine and Vaccine Boosters in Urban Bangkok, Thailand: A Cross-Sectional Study

Abstract: Background: COVID-19 vaccine hesitancy is a global concern. Many individuals are concerned about the potential side-effects of the COVID-19 vaccine and vaccine boosters. The purpose of this study was to assess attitudes and satisfaction concerning COVID-19 vaccines and vaccine boosters in the population in Bangkok, Thailand. Methods: A cross-sectional online survey measuring COVID-19 vaccine attitudes and satisfaction was distributed from September to December 2021. Multiple linear regression was used to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Age above 45 and the male gender were strong predictors detected in [ 41 , 54 , 60 , 61 , 69 , 74 , 78 , 81 ]. Educational level was a strong predictor as well, according to several included studies [ 28 , 37 , 45 , 52 , 61 , 65 , 68 , 69 , 70 , 72 , 76 ]. Being a HCW was another predictor in 2 studies [ 48 , 74 ], while a previous COVID-19 infection in the family was a predictor in 5 studies [ 28 , 49 , 60 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age above 45 and the male gender were strong predictors detected in [ 41 , 54 , 60 , 61 , 69 , 74 , 78 , 81 ]. Educational level was a strong predictor as well, according to several included studies [ 28 , 37 , 45 , 52 , 61 , 65 , 68 , 69 , 70 , 72 , 76 ]. Being a HCW was another predictor in 2 studies [ 48 , 74 ], while a previous COVID-19 infection in the family was a predictor in 5 studies [ 28 , 49 , 60 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Employment status and personal/household income were predictors among several studies [ 47 , 51 , 56 , 61 , 72 , 76 , 81 ]. Having a history of chronic disease has been reported to be a predictor of booster dose acceptance in several studies [ 28 , 37 , 39 , 49 , 51 , 69 , 79 ], while other studies reported trust in the effectiveness of the vaccine and the fear of an unknown adverse effect as significant determinants of booster dose acceptance [ 35 , 37 , 42 , 51 , 66 , 67 , 70 , 75 , 77 , 78 , 79 ]. Among different populations, history of chronic disease and trust in the vaccine effectiveness were significant predictors through our linear regression model, which explained 39% of the predictors involved in COVID-19 booster dose acceptance: 8151 (95% CI: 2236–14064, p = 0.008) and 6548 (95% CI: 935–12159, p = 0.023, Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…The intention to seek annual vaccination is similar to repurchase intention [ 29 ]. Satisfaction level with previous COVID-19 vaccination may influence decision making about receiving annual boosters [ 30 ]. We included demographic factors (e.g., age, gender, educational level, and socio-economic position) [ 31 , 32 ], and cognitive constructs from health behavior theories, such as the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB), as potential factors in this study because they have been widely used in the context of vaccination intention, such as influenza and COVID-19 vaccine [ 23 , 24 , 33 , 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…More scientific, accurate, and supportive information about the satisfying protective effects of the booster dose of COVID‐19 vaccines was supposed to be conveyed to the public through established publicity channels such as social media, local hospital physicians, and the government. 46 , 47 At the same time, in the absence of disclosure and definition of AE by mainstream media, the amplifying effect of misinformation on vaccine AE via social media should be given enough attention. Although the participants in this study showed the strong confidence in vaccines' effectiveness, their attitudes may be easily altered by biased information and rumors.…”
Section: Discussionmentioning
confidence: 99%
“…We should be alert to the potential growing fatigue feelings toward the pandemic in populations. More scientific, accurate, and supportive information about the satisfying protective effects of the booster dose of COVID‐19 vaccines was supposed to be conveyed to the public through established publicity channels such as social media, local hospital physicians, and the government 46,47 . At the same time, in the absence of disclosure and definition of AE by mainstream media, the amplifying effect of misinformation on vaccine AE via social media should be given enough attention.…”
Section: Discussionmentioning
confidence: 99%